2020
DOI: 10.1002/jbmr.4141
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fractures Before and After Dialysis Initiation

Abstract: Fractures are common in dialysis patients, but little is known about the trajectory of incidence rates of different types of fractures before and after dialysis initiation. To address this, we investigated the incidence of major fractures before and after dialysis initiation. We performed a retrospective statistical analysis using the Swedish Renal Registry of 9041 incident dialysis patients (median age 67 years, 67% men) starting dialysis 2005 through 2015 to identify major fractures (hip, spine, humerus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(73 reference statements)
0
6
0
1
Order By: Relevance
“…7,8 Epidemiologic studies have shown that dialysis patients have a higher hip fracture risk than nondialyzed CKD patients and the general population. [9][10][11][12] Hip fracture is the most prevalent type of fracture in dialysis patients, and subsequent high mortality is well described. 11 Therefore, preventing hip fractures is crucial for achieving better clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Epidemiologic studies have shown that dialysis patients have a higher hip fracture risk than nondialyzed CKD patients and the general population. [9][10][11][12] Hip fracture is the most prevalent type of fracture in dialysis patients, and subsequent high mortality is well described. 11 Therefore, preventing hip fractures is crucial for achieving better clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A study using the Swedish Renal Registry 17) found that the incidence rate of hip fractures began to sharply increase 3 months before dialysis initiation, peaked at initiation, and then declined thereafter. In contrast, the incidence rate of non-hip fractures remained stable during the transition period and gradually increased over time.…”
Section: Fractures Of Ckd Patientsmentioning
confidence: 99%
“…Risk factors of fractures after KT include older age, female sex, diabetes, dialysis vintage before transplantation, previous history of fracture, and receipt of a kidney from a deceased donor rather than a living one. 18) While hip fractures are more common among dialysis patients, 16 17) studies 22 23) have shown that peripheral fractures, such as forearm or foot fractures, may be more common than hip fractures after KT. Although the overall incidence of hip fractures in HD patients is higher than that in PD or KT patients during the first 1 to 3 years after KT, the incidence of hip fractures among KT patients exceeds that among dialysis patients.…”
Section: Fractures Of Ckd Patientsmentioning
confidence: 99%
“…The spectrum includes disorders in bone turnover, impaired mineralization, and changes in bone volume (82,83). These abnormalities cause decreased mechanical strength with increased risk of fractures (84,85), and altered mineral metabolism with increased risk of ectopic calcification (86). Malluche et al reported a series of 630 bone biopsies from patients with CKD on dialysis.…”
Section: Bone Metabolismmentioning
confidence: 99%